Cerebroprotection by the neuronal PGE(2) receptor EP2 after intracerebral hemorrhage in middle-aged mice - Wu, He (J Cereb Blood Flow Metab, 2016)
Inflammatory responses mediated by prostaglandins such as PGE(2) may contribute to secondary brain injury after intracerebral hemorrhage (ICH). However, the cell-specific signaling by PGE(2) receptor EP2 differs depending on whether the neuropathic insult is acute or chronic. Using genetic and pharmacologic approaches, we investigated the role of EP2 receptor in two mouse models of ICH induced by intrastriatal injection of collagenase or autologous arterial whole blood. We used middle-aged male mice to enhance the clinical relevance of the study. EP2 receptor was expressed in neurons but not in astrocytes or microglia after collagenase-induced ICH. Brain injury after collagenase-induced ICH was associated with enhanced cellular and molecular inflammatory responses, oxidative stress, and matrix metalloproteinase (MMP)-2/9 activity. EP2 receptor deletion exacerbated brain injury, brain swelling/edema, neuronal death, and neurobehavioral deficits, whereas EP2 receptor activation by the highly selective agonist AE1-259-01 reversed these outcomes. EP2 receptor deletion also exacerbated brain edema and neurologic deficits in the blood ICH model. These findings support the premise that neuronal EP2 receptor activation by PGE(2) protects brain against ICH injury in middle-aged mice through its anti-inflammatory and anti-oxidant effects and anti-MMP-2/9 activity. PGE(2)/EP2 signaling warrants further investigation for potential use in ICH treatment.